Acute porphyria: an unusual case of quadriparesis, hypertension, recurrent severe cyclic abdominal pain, and seizures - Gowa, Murtaza Ali; Abidi, Syed Muhammad Aqeel; Khan, Momina; Jamal, Ghazala; Nawaz, Hira (Journal of the Pakistan Medical Association, 2023)
Porphyria refers to a rare group of genetically inherited or acquired disorders that arise due to reduced metabolic activity of any of the enzymes in the haem biosynthetic pathway. Defect in any enzyme causes the presentation of symptoms of porphyria. The epidemiology of Acute Intermittent Porphyria (AIP) is complicated because of its rarity and delay in diagnosis. We present the case of a seven-year-old girl who presented with multisystem involvement; her symptoms were quadriparesis, hypertension, recurrent severe cyclic abdominal pain, and seizures. These symptoms together were not explained by the differentials taken into account. She presented before puberty with no family history of such conditions, while being born of consanguineous marriage. Her symptoms along with urinary porphobilinogen positivity test helped to reach the diagnosis of AIP in the absence of cutaneous manifestations. ---Continue